Analysis of the Formation and Development of Anti-Narcotics Cadres to Prevent and Overcome the Impact of Narcotics According to the Narcotics Law Number 9 of 1999 on Minors in Medan Johor District, Medan City, North Sumatra Province - Maysarah; John Simon (International Journal of Global Sustainable Research, 2023)
This research aims to describes the object that is the main problem and analyzes it with the aim of drawing a conclusion. Because it is hoped that it will be able to provide a detailed, systematic and comprehensive description of the object of study to be researched. As for other things, there is a lack of treatment for underage drug addicts, as well as the lack of costs to bring in resource persons and internet access to obtain information regarding types of narcotics, prevention, action, treatment by rehabilitating victims due to narcotics addiction and punitive sanctions for those who violate the law. Narcotics No.35 of 2009. So in Medan Johor District, North Sumatra Province, the Community Service Team from Dharmawagsa University felt that it was very necessary to carry out outreach regarding the Implementation of Narcotics Law Number 35 of 2009 on the dangers as well as their formation and handling in Medan Johor District, so that with socialization, the Service Team hopes to be right on target with the community by providing information regarding dangers, forming volunteers, posts for public complaints and narcotics abuse, as well as matters relating to the formation of anti-narcotics volunteers and information regarding procedures for forming, overcoming and rehabilitating victims of narcotics addiction.